An Axiomatic Approach in the Development of the Theory of Creative Aging - Jose Mari Louis G. Alforque (IJNP (Indonesian Journal of Nursing Practices), 2022)
Background: There are several ways in which the term ‘creativity; is defined.  It may be considered an ‘act’ or an ‘expression’.  At an earlier age, people do things in accordance with what is expected of them and moreover, do things from their perspective.  In older adults, creativity is an innate characteristic developed to improve oneself, and on the other hand, an ‘expression’, a way of doing things in everyday life.Objective: This study aimed to develop a substantive theory of creative aging among older adults.Methods:  The theory was developed using an axiomatic approach where six axioms were deduced into three emergent propositions. It is theorized that creativity is an innate ability of a person that does not stop upon reaching old age, and is motivated by factors that may limit or enhance creativity.Result: The expression of creativity among older adults in the later years is dynamic and a continuous engagement in activities and life pursuits leads to a healthier and more productive state of aging.Conclusion: Providing opportunities and an avenue where older adults can express their creativity should be considered to better understand the life of older adults and how they continue to flourish in their later years.